GENETIC DIVERSITY AND DNA FINGERPRINTING OF POTATO VARIETIES USING SIMPLE SEQUENCE REPEAT (SSR) MARKERS - S. U. Rahman; S. Jamil; R. Shahzad; E. Yasmeen; S. Sattar; M. Z. Iqbal (Journal of Animal and Plant Sciences, 2022)
DNA fingerprinting is a tool for plant breeder rights protection, and variety registration in Plant Breeder Rights Repository. In the present study, we developed a DNA fingerprinting profile of 12 potato cultivars grown in Punjab Pakistan using 214 informative Simple Sequence Repeat (SSR) markers. A total of 1720 alleles were amplified by 214 SSR with an average of 8.04 alleles per marker. Approximately 72% of amplified alleles (1329 alleles) were polymorphic with 6.88 polymorphic alleles per SSR marker. The number of alleles ranged from 1 to 31. Similarly, polymorphic alleles per marker ranged from 0 to 24. A maximum number of alleles and polymorphic alleles were reported by IBR13 marker. The Polymorphic information content (PIC) value ranged from 0 to 0.96. The average PIC value for 214 amplified markers was 0.73. Collectively, 72 SSR markers amplified unique allelic patterns for DNA fingerprinting. Potato varieties Rubby and Sadaf were identified by 15 SSR markers whereas Faisalabad Red and SH-5 were identified by 12 SSR markers. Cluster and structure analysis classify the potato genotypes into two distinct groups. This information will be useful for the variety registration process and will provide a platform for future DNA fingerprinting and genetic diversity studies for the choice of SSR markers.
Keywords: Cluster analysis; Genetic diversity; Polymerase Chain Reaction; Polymorphic Information Content; Variety identification